Generation of Sweet Orange Transgenic Lines and Evaluation of Citrus psorosis virus-derived Resistance against Psorosis A and Psorosis B - Andrea Reyes, Carina; Cecilia Zanek, Maria; Velázquez, Karelia; Costa, Norma; Ines Plata, Maria; Laura Garcia, Maria (2017)
Citrus psorosis is a widespread serious disease of citrus caused by Citrus psorosis virus (CPsV). In Argentina and Uruguay, this disease is spread by an unknown vector and there is no natural resistance or tolerance to the disease. There are two types of psorosis, described according to the symptoms observed in citrus trees, psorosis A (PsA) and psorosis B (PsB). PsA protects against the severe effects of the more aggressive type PsB. We have applied pathogen-derived resistance to create a defence mechanism against this virus disease. Sweet orange transgenic lines were obtained containing three different genes of CPsV (54k, 48k and 24k genes) taken from a PsA isolate (CPV-4). Fourteen lines were selected containing 1, 2 or 3 copies of the transgenes and evaluated for their acquired resistance against PsA (CPV 4 from USA) and PsB (CPsV 189-34 from Argentina) isolates. These lines were susceptible to both isolates when graft-infected, although one of the lines carrying the cp gene (CP-96 line) containing two copies of the transgene and expressing a low level of the coat protein showed a delay in symptom expression when inoculated with the PsB isolate.